Deformation and damage of random fibrous networks. (February 2020) - Sozumert, Emrah; Farukh, Farukh; Sabuncuoglu, Baris; Demirci, Emrah; Acar, Memis; Pourdeyhimi, Behnam; Silberschmidt, Vadim V.
Highlights: Damage and fracture mechanisms of fibrous networks are investigated. A combined experimental and numerical (finite-element) study is implemented. Effects of notch shape on deformation localization and damage evolution are studied. A notch in fibrous networks does not cause a significant increase in localized strain. Abstract: Fibrous networks are encountered in various natural and synthetic materials. Typically, they have random microstructures with complex patterns of fibre distribution. This microstructure, together with significant (in many cases) stretchability of such networks, results in a non-trivial load-transfer mechanism, different from that of continuous media. The aim of this study is to investigate evolution of local deformation, damage and fracture processes in fibrous networks. In order to do this, together with extensive experiments, discontinuous finite-element (FE) models with direct incorporation of microstructural features were developed using a parametric approach for specimens with various dimensions and different types of notches. These models, mimicking a microstructure of the selected fibrous network, were loaded by stretching along a principal direction. Discontinuous FE models provided data not only on a global response of the specimens but also on levels of stresses and strains in each fibre, forming the network. An effect of a notch shape on evolution of fibre strains as well as mechanisms and patterns of damage was investigated using experimental data and simulation results, assessing also toughness of specimens. Strain distribution over selected paths were tracked in notched specimens to quantify strain distributions in the vicinity of notch tips. The growth and patterns of local damage due to axial stretching obtained in advanced numerical simulations with the developed FE models demonstrated a good agreement with experimental observations. Graphical abstract : Image, graphical abstract